Emerging molecular mechanisms of vascular dementia. Issue 3 (May 2019) - Romay, Milagros C.; Toro, Camilo; Iruela-Arispe, M. Luisa
Abstract : Purpose of review: Microvascular ischemic disease of the brain is a common cause of cognitive impairment and dementia, particularly in the context of preexisting cardiovascular risk factors and aging. This review summarizes our current understanding of the emerging molecular themes that underlie progressive and irreparable vascular disease leading to neuronal tissue injury and dementia. Recent findings: Cardiometabolic risk factors including diabetes and hypertension are known to contribute to vascular disease. Currently, the impact of these risk factors on the integrity and function of the brain vasculature has been target of intense investigation. Molecularly, the consequences associated with these risk factors indicate that reactive oxygen species are strong contributors to cerebrovascular dysfunction and injury. In addition, genetic linkage analyses have identified penetrant monogenic causes of vascular dementia. Finally, recent reports begun to uncover a large number of polymorphisms associated with a higher risk for cerebrovascular disease. Summary: A comprehensive picture of key risk factors and genetic predispositions that contribute to brain microvascular disease and result in vascular dementia is starting to emerge. Understanding their relationships and cross-interactions will significantly aid in the development of preventive and intervention strategies for this devastating condition.